Comparative arsenic tolerance and accumulation potential between wild Tagetes patula and Tagetes minuta - Shahzadi, Irum; Shah, Mohammad Maroof; Akhtar, Irrum Saleem; Ismail, Tariq; Ahmad, Raza; Nawaz, Ismat; Siddique, Maria; Baig, Sofia; Baig, Ayesha; Waheed, Ummara (Penerbit Universiti Kebangsaan Malaysia, 2022)
Arsenic (As) is a bioactive metalloid that is highly toxic to humans, animals, and plants. Environmental contamination of As especially in groundwater increases due to natural and anthropogenic activities. The present study was performed to evaluate the potential of wild Tagetes species for the phytoremediation of As contaminated soil/water. This comparative research aims to analyze As accumulation and tolerance in two wild species of Tagetes, T. minuta and T. patula. The 20 days old seedlings were grown hydroponically and exposed to the different concentrations of As, 0, 50, 150, and 300 µM As2 O3 for 1-, 4- and 7- days intervals.Effect of As stress was measured on the rate of seed germination, growth parameters like fresh and dry biomass weight, root/shoot length, chlorophyll contents and As contents in root and shoot in both Tagetes species. Increasing concentration of As restricts the growth activity of T. minuta with toxicity symptoms on leaves such as chlorosis. Accumulation of As in the shoot was significantly (p ≤ 0.01) high (634 µg g-1 DW) in T. patula as compared to T. minuta (397 µg g-1 DW) at 300 µM As2 O3 . Both Tagetes species exhibited high variation for As tolerance parameters as well as for As accumulation patterns. Comparatively good tolerance and accumulation of As in T. patula suggests that this species could be used in phytoextraction and re-vegetation in As contaminated sites.